Pathways from Digital Literacy to Teaching Effectiveness: The Mediating Effects of Instructional Leadership, Pedagogical Innovation, and Technology Self-Efficacy - Novia Eka Pratiwi (Progressive Journal of Educational Science, 2026)
This study aims to examine the influence of Digital Literacy, Instructional Leadership, Pedagogical Innovation, and Technology Self-Efficacy on Teaching Effectiveness among elementary school teachers in Ponorogo Regency. A total of 119 teachers were selected as respondents using purposive sampling, based on the criteria of being active teachers with experience in applying educational technology. The research instrument was developed from construct indicators and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results reveal that Digital Literacy significantly affects Instructional Leadership and Technology Self-Efficacy but does not significantly influence Pedagogical Innovation. Instructional Leadership strongly impacts both Pedagogical Innovation and Teaching Effectiveness, while Pedagogical Innovation contributes positively but modestly to Teaching Effectiveness. Furthermore, Technology Self-Efficacy emerges as an effective mediator linking Digital Literacy to Teaching Effectiveness. Notably, this study offers novel empirical evidence from elementary school teachers in Ponorogo, Indonesia, a relatively under-studied educational context, thereby extending the existing literature on instructional leadership, digital literacy, and teaching effectiveness in the digital era.